Peran Tutor Dalam Meningkatkan Motivasi Belajar Peserta Didik Program Pendidikan Kesetaraan Paket C - Bunga Ika Parwati; Rivo Nugroho (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
The rigid interaction between educators and students causes students not to be motivated to learn. This study uses a qualitative approach. This research was conducted at UPTD SPNF SKB Magetan. The subjects in this study were tutors at UPTD SPNF SKB Magetan. Data collection techniques in-depth interviews, participatory observation and documentation. Testing the validity of data in qualitative research includes testing credibility (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity). Data analysis techniques consist of three components of analysis, namely data reduction, data presentation and conclusion. The results of the study show that tutors can conduct studies as informants by providing basic information to students, as motivators by providing an overview of the learning output that will be obtained by students, as guides through directing the effectiveness of learning to students, as facilitators by providing forums for consulting students regarding learning difficulties and needs, as an evaluator through regular monitoring of student development. Keywords: tutor role, learning motivation, equality education, non-formal education